1999
DOI: 10.1007/s003950050129
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a long-surviving murine model of myocardial infarction: Qualitative and quantitative conventional microscopic findings during pathological evolution

Abstract: Ongoing basic molecular analyses are being performed in mice, and a simple long-surviving murine model of myocardial infarction (MI) would be very useful in this regard. Although a few studies have induced MI in mice by coronary artery ligation, the induction involves a complex technique and has a relatively high mortality rate. In addition, the identification of the basic pathological sequence is essential to the interpretation of experimental results. We developed a simple technique for the induction of MI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…In the latter case, the MI is usually nontransmural. Animals with a smaller MI, unintentionally induced by ligation of the LMDA, have usually been removed from published study data analyses (7,11), or their results have been presented separately (1a, 10), because those hearts did not show significant remodeling or functional decline. For instance, Bayat et al (1a) reported that morphometric and functional indexes derived from echocardiography of mice with MI Ͻ30% of the LV (16 Ϯ 3% of the LV) were not different from those of sham-operated animals 6, 12, or 18 wk after coronary ligation.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, the MI is usually nontransmural. Animals with a smaller MI, unintentionally induced by ligation of the LMDA, have usually been removed from published study data analyses (7,11), or their results have been presented separately (1a, 10), because those hearts did not show significant remodeling or functional decline. For instance, Bayat et al (1a) reported that morphometric and functional indexes derived from echocardiography of mice with MI Ͻ30% of the LV (16 Ϯ 3% of the LV) were not different from those of sham-operated animals 6, 12, or 18 wk after coronary ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial access was achieved by a left thoracotomy. Occlusion of the first branch of the left anterior descending coronary artery was performed by thermocoagulation, 19 and vessel occlusion was confirmed by a blanching in surface color. Viable 3DFC or nonviable 3DFC patches (4-mm diameter) were sutured (10-0 Prolene suture; Ethicon Corp) onto the epicardial surface over the ischemic region.…”
Section: Coronary Occlusion and Implant Surgerymentioning
confidence: 99%
“…In the literature, both large-animal (mainly canine and porcine) 8 -10 and small-animal (including lupine and rodent) [11][12][13] models have been used for both acute and chronic models of coronary vessel occlusion. In the acute model, a coronary vessel is occluded by suture ligature, cryoprobe, cautery probe, or microembolization coils, 10,[12][13][14] thereby stimulating an immediate infarction in which intrinsic collateralization of the heart is insufficient to rescue cardiac function and dead cardiomyocytes are replaced by fibrotic scar tissue. Although the infarcted region will grow and the myocardial wall will thin, hibernating cardiomyocytes surrounding the infarcted zone may be temporarily supported nutritionally.…”
mentioning
confidence: 99%
“…Although there have been studies employing a mouse model of MI (Kumashiro et al 1999;Lutgens et al 1999), they have focused mostly on the changes seen during the first few weeks post-MI. Lutgens et al (1999) recently observed LV dilatation, hypertrophy and collagen deposition at 1, 2, 3 and 5 weeks post-MI and these structural changes were associated with decreased dP/dt (maximum increase in pressure over time).…”
mentioning
confidence: 99%
“…Lutgens et al (1999) recently observed LV dilatation, hypertrophy and collagen deposition at 1, 2, 3 and 5 weeks post-MI and these structural changes were associated with decreased dP/dt (maximum increase in pressure over time). Kumashiro et al (1999) also conducted a semi-quantitative analysis of total inflammatory cell infiltration, fibrosis and vascular proliferation by 4 weeks after MI. However, precise quantitative data on histopathological and morphological changes post-MI in a mouse model are lacking.…”
mentioning
confidence: 99%